0640 Initial Sleep Center Evaluation and Follow Up Improves Positive Airway Pressure (PAP) Therapy Adherence When Compared to Direct Referrals Without Sleep Physician Follow Up: A Retrospective Study. (27th May 2020) - Aljarod, T; Tran, L; Al Ikhwan, M; Prasad, B
Abstract: Introduction: Obstructive sleep apnea (OSA) affects 26% of adults and positive airway pressure (PAP) is the gold-standard of therapy. Factors affecting PAP adherence—use >4 hours in a 24-hour period—have been studied extensively. We compared of the three months (or other time frame) PAP adherence between patients seen by a sleep specialist prior to OSA diagnosis versus patients referred directly for OSA testing by non-sleep specialist providers. The goal of the study was to understand the impact of sleep consultation on PAP adherence. Methods: Direct referral (DR) patients underwent polysomnography (PSG) and received PAP devices prior to the sleep clinic visit. In contrast, sleep center patients (SC) had a sleep clinic visit with a sleep physician or APRN prior to PSG. Eighty-four patients were included in this study, 42 DR and 42 SC patients. Exclusion criteria were age <18 years old, absence of baseline PSG, and lack of 90-day compliance data. Covariates included demographics, body mass index (BMI), AHI, nadir oxygen saturation, demographics, and Epworth Sleepiness Scale (ESS) score. Objective PAP adherence for first 90 days was the primary outcome. Results: Age (p=0.1), ESS (p=0.3), BMI (p=0.6), and AHI (p=0.9) were not significantly different between the groups. SC patients had greater PAP adherence (4.77 hours, 95%CI: 4.1 to 5.4) compared to DR patients (3.61 hours, 95%CI: 2.88 to 4.33, p=0.02). SC patients were also 8 times more likely to follow up in clinic within 1 year of starting PAP treatment (Likelihood Ratio 8.25, p=0.004). Conclusion: While possibly more time-efficient for patients, direct referrals may ultimately result in lower PAP adherence due to missed opportunities for receiving education about OSA and PAP therapy. This is consistent with findings from a previous meta-analysis demonstrating that educational interventions improve PAP adherence. Moving forward, we will continue encouraging directly referred patients to follow up in the sleep center after PSG. Support: None